KEPAILITAN TERHADAP HARTA PENINGGALAN DALAM PERSPEKTIF HUKUM EKONOMI SYARI’AH TELAAH PASAL 207 UNDANG-UNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG - Ningsih, Oktaria; Fauziah, Fauziah; Fitriyati, Yusida (Muamalah, 2019)
ABSTRACT In line with the development of bankruptcy regulations in Indonesia, there was also bankruptcy of inheritance in which Article 207 of Law Number 37 Year 2004 concerning Bankruptcy and Delay of Debt Payment Obligations stated that "Property of the deceased must be declared bankrupt, if two or more creditors submit a request for it and briefly prove that (1) the debt of the person who died, during his lifetime was not paid in full and (2) at the death of the person, his inheritance is not enough to pay his debt. "Therefore this thesis is titled Bankruptcy Against Property in the Perspective of Shari'ah Economic Law Study Article 207 of Law Number 37 Year 2004 concerning Bankruptcy and Delay of Obligation to Pay Debt. The problems that will be raised in writing this essay are how to settle bankruptcy on assets according to Law Number 37 of 2004 concerning Bankruptcy and Delaying Obligations of Debt Payments and how the Shari'ah Economic Law reviews the bankruptcy of inheritance. The research methodology in writing this paper uses a type of literature study (Library Research) that emphasizes the source of information from various literature, the data collection techniques in this study are research with Library Studies. Then the data is analyzed using qualitative descriptive analysis method. Based on the results of the discussion, it was concluded that bankruptcy based on Law Number 37 of 2004 concerning Bankruptcy and Delay of Debt Payment Obligations could also be ruled out by bankruptcy statements. The decision on the Bankruptcy Statement has the effect of legally separating the assets of the deceased from the assets of his heirs. In Syari'ah Economic Law bankruptcy is called Taflis. Bankruptcy is caused by debtor debts that are due. Someone has died who was declared bankrupt, the person who is obliged to pay off the debt is his heir. provided that the heir's responsibility for the heir's debt is limited. Keywoard: Bankruptcy and inheritance.